Molecular Surveillance and Ex Vivo Drug Susceptibilities of Plasmodium vivax Isolates From the China–Myanmar Border - Zeng, Weilin; Zhao, Hui; Zhao, Wei; Yang, Qi; Li, Xinxin; Li, Xiaosong; Duan, Mengxi; Wang, Xun; Li, Cuiying; Xiang, Zheng; Chen, Xi; Cui, Liwang; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Drug resistance in Plasmodium vivax may pose a challenge to malaria elimination. Previous studies have found that P. vivax has a decreased sensitivity to antimalarial drugs in some areas of the Greater Mekong Sub-region. This study aims to investigate the ex vivo drug susceptibilities of P. vivax isolates from the China–Myanmar border and genetic variations of resistance-related genes. A total of 46 P. vivax clinical isolates were assessed for ex vivo susceptibility to seven antimalarial drugs using the schizont maturation assay. The medians of IC50 (half-maximum inhibitory concentrations) for chloroquine, artesunate, and dihydroartemisinin from 46 parasite isolates were 96.48, 1.95, and 1.63 nM, respectively, while the medians of IC50 values for piperaquine, pyronaridine, mefloquine, and quinine from 39 parasite isolates were 19.60, 15.53, 16.38, and 26.04 nM, respectively. Sequence polymorphisms in pvmdr1 (P. vivax multidrug resistance-1), pvmrp1 (P. vivax multidrug resistance protein 1), pvdhfr (P. vivax dihydrofolate reductase), and pvdhps (P. vivax dihydropteroate synthase) were determined by PCR and sequencing. Pvmdr1 had 13 non-synonymous substitutions, of which, T908S and T958M were fixed, G698S (97.8%) and F1076L (93.5%) were highly prevalent, and other substitutions had relatively low prevalences. Pvmrp1 had three non-synonymous substitutions, with Y1393D being fixed, G1419A approaching fixation (97.8%), and V1478I being rare (2.2%). Several pvdhfr and pvdhps mutations were relatively frequent in the studied parasite population. The pvmdr1 G698S substitution was associated with a reduced sensitivity to chloroquine, artesunate, and dihydroartemisinin. This study suggests the possible emergence of P. vivax isolates resistant to certain antimalarial drugs at the China–Myanmar border, which demands continuous surveillance for drug resistance.